Analisis Marxis terhadap Ketimpangan Akses dan Distribusi Kekayaan di Clarion-Clipperton - Syarifah, Claudia; Omarrosi, Syafrilla (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
This article explores the opportunities and challenges of seabed exploration in â€œThe Area,â€ with a specific focus on the potential for seabed mining in regions like the Clarion-Clipperton Zone, considered the common heritage of humankind. While the maritime sector holds promise for future exploration, these opportunities are predominantly accessible to technologically advanced, developed nations, resulting in a profound injustice for developing countries. This paper underscores the principle that